Enhancing horticultural productivity, incomes and livelihoods through integrated management of aphid pests on vegetables in sub-Saharan Africa - Hanna, R.; Fotso-Kaute, A.; Kumar, P.L.; Djomaha, E.; Toukem, N.; Dongmo, M.; Doumtsop, A.; Ramasamy, S.; Abang, A.; Ekesi, S.; Mohamad, S.; Bayissa, W.H.; et al. (International Institute of Tropical Agriculture, 2016)
Through several surveys and field trials we determined species composition and distribution of aphids as well as virus incidence on okra and cabbage in Cameroon and okra and kale in Kenya. On cabbage and kale, the cabbage aphid and false turnip aphid were, respectively, most important in higher and lower altitudes. The cabbage aphid in Kenya was associated with both specialist and generalist natural enemies whereas in Cameroon the specialist parasitoid Diaeretiella rapae was absent. Attempts to introduce this parasitoid into Cameroon failed, perhaps because of specific differences in cabbage aphid hosts from Cameroon and Kenya. No parasitoids were associated with the false turnip aphid regardless of location. On okra, the cotton aphid (Aphis gossypi) was the most abundant and widespread, but the leaf beetle Nistora uniformis turned out to be the major pest of okra, surpassing the importance of aphids in some locations. Regardless of country, aphids attracted heavy use of pesticides which upset the existing guild of natural enemies that could otherwise reduce aphid populations to acceptable levels, as we determined during details field trials in both Cameroon and Kenya. The components of an integrated program for the control of aphids on okra, cabbage, and kale have been identified. This program singly or in several combinations are likely to result in considerable reduction in the use of broadspectrum pesticides and in improved productivity and profitability of vegetables with lower pesticide residues.